The Application of Restorative Justice Toward Children as Criminal in Indonesia: Array - Anggraeni, RR. Dewi; Imanuddin, Iman; M., Aidil (Acta Universitatis Danubius. Juridica, 2021)
This study aims to know the function of judge application of restrorative justice in immoral behaviour, especially sex on children, which written on verdict number 49/Pid.Sus-Anak/2019/PN.Tng. Qualitative methodology is used as the research methodology with library research as the data collection technique. The data is taken from Law on Children Protection (No.35/2014), books, and related literature. The results showed that the conviction process given to children through formal criminal justice system, by putting them to the jail, cannot guarantee to give detterent effect and make them a better person. Yet, prison will make them become smarter in doing criminal. Judge is suppossed to put forward the children’s necessary and future, even if, juridically, the behaviour can be categorized as the criminal act. However, it is hoped that there is another action, beside being prisoned, that can give detterent effect for children who commit crime. Moreover, the set of legal process done on children's criminal is a disserve thing, either for the perpetator or the victim.